Persatuan dan Kerjasama Adalah Kunci Utama Membangun Teman Sejati di Sekolah - Fratama, Anggara Surya; Sulistiyawati, Ica; Meilani, Tantri; Nayoan, Calista Priscillia Pingkan; Salsabilah, Aulia; Aproditha, Aulia Nisvia; Hayati, Auliya Aenul (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the effectiveness of a pocket book as a learning medium for teaching the values of cooperation and unity among third-grade elementary school students. The research employs a mixed-methods approach using an embedded concurrent design, which integrates quantitative and qualitative data simultaneously. Quantitative data were collected through a Likert scale questionnaire, while qualitative data were obtained from interviews, observations, and documentation. The research subjects included 22 students, 21 parents, and 1 teacher at SD Negeri 1 Mayung, Cirebon. The findings show that 91% of students strongly agreed that the pocket book enhanced cooperation, and 86% strongly agreed that it improved the value of unity. Qualitative data from interviews and observations support these results, indicating positive changes in students’ attitudes, such as increased empathy, collaboration, and responsibility, both at school and at home. The teacher also stated that the pocket book contributed to creating an inclusive and reflective learning environment. The conclusion of this study is that the narrative-visual and contextual-based pocket book is effective in instilling the character values of cooperation and unity. The active involvement of parents and teachers also supports the successful implementation, and this pocket book is suitable for replication to strengthen character education in elementary schoolsers.